ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR - Ermeila, Sri (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2017)
This study aims to determine the factors that affect consumer behavior onpurchasing decisions of motorcycle brand "Honda" in the city of Palembang. Along withthe development of the era and the increasing need for transfortasi tools bring fresh airfor automotive companies, especially motorcycle companies which are very much neededby many people in addition to affordable and easy to maintain. One brand that is liked bymost people is the Honda brand. The sample in this study amounted to 100 people takenfrom the respondents of motorcycle users of honda brand domiciled in the city ofPalembang by using purposive sampling technique. The method of analysis usingmultiple linear regression method. Consumer behavior factors both simultaneously andpartially affect the purchasing decision of honda motorcycle brand in Palembang city